Identification of large genetic variations in the equine infectious anemia virus tat-gag genomic region - Cursino, Andreia Elisa; Lima, Maurício Teixeira; Nogueira, Márcia Furlan; de Aguiar, Daniel Moura; Franco Luiz, Ana Paula Moreira; Alves, Pedro Augusto; Araujo Junior, João Pessoa [UNESP]; Kroon, Erna Geessien (Hindawi, 2020)
The aetiological agent of equine infectious anaemia (EIA) is the retrovirus equine infectious anemia virus (EIAV) that infects all members of the Equidae family. The EIA is widely disseminated in the Brazilian territory with a high seroprevalence in the Brazilian Pantanal and is mainly diagnosed using agar gel immunodiffusion (AGID). There are few complete EIAV genome sequences available in GenBank, which had an impact on molecular detection studies. In this study, we conducted molecular detection and sequencing of EIAV proviral DNA from Brazilian horses. We analysed the genomic region from exon 1 of tat to gag (tat-gag). Comparative serological tests, comprising AGID and two enzyme-linked immunosorbent assays (ELISAs), were also conducted. Of the 133 samples, 58 were positive in the tat-gag PCR, and 49 nucleotide sequences of 272 bp were obtained. Using this developed tat-gag PCR EIAV proviral DNA was detected in 7% of the AGID-negative samples and 26% of the AGID-negative samples were positive in at least one of the ELISA tests used. Using phylogenetic analysis, the Brazilian Pantanal EIAV sequences grouped in a different clade of EIAV sequences from other countries. Thus, the EIAV sequences can contribute to the knowledge of the tat-gag genomic region in the circulating viruses in the Brazilian Pantanal, in addition to providing new information about the genetic diversity. In addition, the serological results demonstrate the greater sensitivity of the ELISAs used in this study compared to AGID for EIA diagnosis.
Keywords: equine infectious anaemia virus; horse; Pantanal; phylogenetic analysis